PKM KELOMPOK PENGOLAH BANDENG PRESTO DI KABUPATEN PANGKEP - Asni, Andi; Kasmawati, Kasmawati; Hamsiah, Hamsiah (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2022)
Milkfish is a fish that has many thorns, so processing is needed to soften the thorns. One of the methods of softening the thorns of whitefish is high-pressure processing (presto). Presto milkfish of various flavors is one of the product diversifications that will become a business and can improve the welfare of coastal communities. The purpose of the community partnership program activities is to provide knowledge about two aspects, namely: 1) production aspects and 2) management aspects. This activity was carried out on July 26, 2019 Gentung Village, Labakkang District, Pangkep Regency The approach method carried out in this community partnership program activity is a participatory method where partners are directly involved in the implementation of activities starting from preparation to the implementation of these activities. Implementation of activities in the form of counseling and demonstrations. The results and external achievements are products with specifications of presto milkfish with various flavors, namely coto flavor, konro flavor, and pallumara taste. The presto milkfish product is packaged and equipped with a label and will be developed into a sustainable home industry business product. One of the ways of marketing taught to partners is by online marketing through applications and social media through WhatsApp, Instagram and Facebook. The hope of this PKM activity is that partners will be more creative and productive, especially in making Bandeng Presto products and making a business that can improve the welfare of the community.